The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/20445911.2021.1900201
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of compound remote associate problems to disruption by irrelevant sound: a Window onto the component processes underpinning creative cognition?

Abstract: Controversy exists regarding the processes involved in creative thinking with the Remote Associates Test (RAT) and the Compound Remote Associates Test (CRAT). We report three experiments that aimed to shed light on the component processes underpinning CRAT performance by using the mere presence of task-irrelevant sound as a key theoretical tool. Experiments 1 and 2 revealed that CRAT performance was impaired relative to a quiet condition by the presence of sequences of changing letters and tones, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 150 publications
(301 reference statements)
0
8
1
Order By: Relevance
“…This finding can be taken as preliminary evidence for a negative relationship between the condensedness of inner speaking and some unique aspect of creative potential that is needed to perform well on the CRAT, but not on the AUT and HMT-S. This might relate to Marsh et al (2021), whose experimental studies suggest that exposing participants to changing tones or speech sounds, which allegedly interferes with inner speech production, diminishes performance on the CRAT. One explanation is that inner speech is needed to form a verbal gestalt of a solution, which is needed for evaluation and which helps to guide further memory search.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This finding can be taken as preliminary evidence for a negative relationship between the condensedness of inner speaking and some unique aspect of creative potential that is needed to perform well on the CRAT, but not on the AUT and HMT-S. This might relate to Marsh et al (2021), whose experimental studies suggest that exposing participants to changing tones or speech sounds, which allegedly interferes with inner speech production, diminishes performance on the CRAT. One explanation is that inner speech is needed to form a verbal gestalt of a solution, which is needed for evaluation and which helps to guide further memory search.…”
Section: Discussionmentioning
confidence: 82%
“…This to establish whether it is indeed the case that the properties and quality of the verbal gestalt that people synthesize to evaluate CRAT solutions, and guide subsequent memory search, is hampered by condensed inner speaking (cf. Marsh et al, 2021). Moreover, the results point toward future research to explain the potentially negative correlation of auditory hallucination proneness with divergent and convergent thinking ability (de Leede-Smith et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that music with lyrics or sounds with comprehensible semantics tends to interfere with understanding cognitive tasks ( Martin et al, 1988 ; Braat-Eggen et al, 2017 ). This idea was also tested in a recent study ( Marsh et al, 2021 ) in which researchers manipulated the intelligibility of auditory materials in background music, and the results showed that the presence of intelligible semantic information (unrelated to the task) in background music impaired participants’ performance in CRATs, compared the control group.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies that found that music interfered with creativity mostly used convergent thinking as the index of creativity. Marsh et al (2021) used the CRAT as a creativity task and concluded that music with understandable semantics interfered with creative performance. Ritter and Ferguson (2017) used the Alternative Use Task (AUT) to assess the effects of music on divergent thinking and used the Remote Association Task (RAT) to evaluate convergent thinking respectively, the results found that listening to “happy” music can increase divergent thinking, but not convergent thinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation